Increased severity of anaemia is associated with 30-day complications following total joint replacement. (April 2020) - Gu, Alex; Malahias, Michael-Alexander; Selemon, Nicolas A.; Wei, Chapman; Gerhard, Eleanor F.; Cohen, Jordan S.; Fassihi, Safa C.; Stake, Seth; Bernstein, Sophie L.; Chen, Aaron Z.; Sculco, Thomas P.; Cross, Michael B.; et al.
Abstract : Aims: The aim of this study was to determine the impact of the severity of anaemia on postoperative complications following total hip arthroplasty (THA) and total knee arthroplasty (TKA). Methods: A retrospective cohort study was conducted using the American College of Surgeons National Quality Improvement Program (ACS-NSQIP) database. All patients who underwent primary TKA or THA between January 2012 and December 2017 were identified and stratified based upon hematocrit level. In this analysis, we defined anaemia as packed cell volume (Hct) < 36% for women and < 39% for men, and further stratified anaemia as mild anaemia (Hct 33% to 36% for women, Hct 33% to 39% for men), and moderate to severe (Hct < 33% for both men and women). Univariate and multivariate analyses were used to evaluate the incidence of multiple adverse events within 30 days of arthroplasty. Results: Following adjustment, patients in the THA cohort with moderate to severe anaemia had an increased odds of 6.194 (95% confidence interval (CI) 5.679 to 6.756; p < 0.001) for developing any postoperative complication. Following adjustment, patients in the TKA cohort with moderate to severe anaemia had an increased odds of 5.186 (95% CI 4.811 to 5.590; p < 0.001) for developing any postoperative complication. Among both cohorts, as severity increased, there was an increased risk of postoperative complications. Conclusion: Preoperative anaemia is a risk factor for complications following primary arthroplasty. There is a significant relationship between the severity of anaemia and the odds of postoperative complications. Patients who had moderate to severe anaemia were at increased risk of developing postoperative complications relative to patients with mild anaemia. When considering elective primary THA or TKA in a moderately or severely anaemic patient, surgeons should strongly consider correcting anaemia prior to surgery if possible. Cite this article: Bone Joint J 2020;102-B(4):485–494.